KEBIJAKAN REFORMASI AGRARIA PADA MASA PEMERINTAHAN JOKO WIDODO DITINJAU DARI KAJIAN HAM DAN GENDER - Erlina Erlina (Riau Law Journal, 2017)
Agrarian Reform, one of the prerequisites in organizing economic development towards a just and prosperous society based on Pancasila, but there are still issues at the level of policy that is interpreted as a product of law, strategy, program and its implementation, especially viewed from human rights and gender studies. Using normative research methods with legal and doctrinal approach, it was found that the policy of Agrarian Reform in Joko Widodo Government era as a product of law and strategy and program has accommodated human rights protection protection although not maximal yet; The agrarian reform policy developed in the era of Joko Widodo Government as a legal product has accommodated gender equality and justice although not yet maximized, but as a strategy and program has not reflected on justice and gender equality